A taxonomic revision of the southwestern Pacific subgenus Hebridosimulium (Diptera: Simuliidae: Simulium) - Craig, Douglas A.; Currie, Douglas C.; Hunter, Fiona F.; Spironello, Mike (Zootaxa, 2006)
Sixteen species, of which 13 are new, in the subgenus Hebridosimulium Grenier & Rageau are now known. Fiji has only Simulium laciniatum, which is widely distributed on five islands. Tahiti has only one species, the enigmatic S. anatolicum. The remaining species are in Vanuatu and known from nine islands, ranging the full length and breadth of the archipelago. Hebridosimulium species are divided among two species groups. The callipygium species group is characterized, in part, by a smooth posterior abdomen in the larvae, and all but one species possess dorsal tubercles on the larval abdomen. Simulium callipygium is the type species, with the tuberculate species in a subgroup comprised of S. banksi, S. johnfrumi, S. pankumuense, and S. tuberculum. The second species group has larvae with the posteroventral abdomen markedly expanded, and all species lack dorsal tubercles. Constituents of the steatopygium species group are S. anatolicum, S. jolyi, S. laciniatum, S. lucyae, S. paradisium, S. steatopygium, S. subparadisium, S. supercilium, and S. undulatum. Two other species of this group, S. adsonense and S. spiroi, of which larvae have markedly pigmented heads, are assigned to the adsonense species subgroup. A chromosome map for Hebridosimulium is established for the first time.